AESTHETIC STUDY OF GENDING BIMANIYU REPERTOIRE OF GENDER WAYANG STYLE TENGANAN KARANGASEM - Hartini, Putu; Sudarta, I Gusti Putu; Muryana, I Ketut (Institut Seni Indonesia Denpasar, 2025)
The gending Bimaniyu of gender wayang is one of Bali's cultural heritage that needs to be preserved. This research can provide an in-depth understanding of the aesthetics of gending, which can help its preservation efforts. The Uniqueness of the Karangasem Style The Karangasem style in the gender gending of the Bimaniyu puppet has characteristics that distinguish it from other styles. This research can reveal the uniqueness of the aesthetics of this style so that it can enrich the cultural treasures of Bali. The specific purpose of this study is to describe the aesthetics of the Gending Bimaniyu style of Tenganan Karangasem. This research will be carried out within 7 months with unique objectives, including a) aesthetics in Gending Bimaniyu style Karangasem and b) Gending Bimaniyu technique style Karangasem. This research is a qualitative descriptive research. The data source was obtained by recording and reviewing the results of the recording of Gending Bimaniyu using a literature method supported by interviews with Gender Wayang artists. The results of the data analysis used to present the results of data analysis are presented by formal and informal methods. The output of this research is in the form of journals, HKI, and teaching materials, which can be used by students and karawitan artists who graduated from ISI Denpasar in analyzing, reconstructing, and displaying a good, correct, and engaging performance composition structure in the Gender Wayang performance.